2006
DOI: 10.1161/01.str.0000226604.10877.fc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk Factors for Stroke

Abstract: Background and Purpose-To estimate the predictive value of risk factors for stroke measured in midlife over follow-up extending through 28 years. Methods-A cohort of 7457 men 47 to 55 years of age and free of stroke at baseline year 1970 were examined. Risk of stroke was analyzed for the entire period and for 0 to 15, 16 to 21, and 22 to 28 years of follow-up using age-adjusted and multiple Cox regression analyses. Results-Age, diabetes, and high blood pressure were independently associated with increased risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 35 publications
(27 reference statements)
2
45
0
Order By: Relevance
“…Per Harmesen et al [15] also found that obesity is a risk factor for stroke (OR = 2.23, 95% C.I. = 1.83 -2.72).…”
Section: Discussionmentioning
confidence: 92%
“…Per Harmesen et al [15] also found that obesity is a risk factor for stroke (OR = 2.23, 95% C.I. = 1.83 -2.72).…”
Section: Discussionmentioning
confidence: 92%
“…Cross-sectional studies conducted in Spanish hypertensive 7 In addition, based on 7457 men aged 47 to 55 years in Sweden with Ͼ20 years follow-up, age, diabetes, blood pressure, and history of transient ischemic stroke, atrial fibrillation, and smoking were associated with a stroke event. 38 Asian reports on a stroke prediction model are also available. First, a Japanese prediction model including all stroke and coronary events for 19 years on 4098 men and 5255 women, aged 50 years, for a 19-year follow-up period showed age, smoking, systolic blood pressure, and serum cholesterol and glucose were included in the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…These covariates did not increase significantly the likelihood ratio test value in the multivariate Cox model. Some lifestyle and socioeconomic factors such as physical activity, 12 household income, 10 and depression 38,42 Figure 2. Nomogram for the risk of stroke incidence in the study participants (nϭ3513).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that diabetes is a strong risk factor for stroke. 22 It has also been shown that high serum triglycerides is a risk factor for stroke in both sexes, [27][28][29] and high BMI has been shown to be a risk factor in men 30 and in women. [31][32][33][34] Fibrinogen levels 35 (not assessed during all of the study period) might also have contributed to the unchanged stroke incidence.…”
Section: Discussionmentioning
confidence: 99%